Digital finance development and manufacturing emission reduction: An empirical evidence from China - Yikun Yin (Frontiers Media S.A., 2022)
The implementation of carbon peak and carbon neutral goals cannot be achieved without the effective support of digital finance. This paper studies the inverted N-curve relationship between digital finance and carbon intensity, and identifies the emission reduction effects of digital finance development from the enterprise level. The study found that the development of digital finance has an inverted-N dynamic impact on the carbon intensity of the manufacturing industry. The emission reduction effects of the development of digital finance have typical multi-dimensional heterogeneous characteristics at the regional and enterprise levels. Mechanism analysis shows that the emission reduction effect of digital finance development depends on the combined effect of scale and technology. The initial stage of digital finance development can promote carbon emission reduction through the "scale effect" of reduction, and the digital finance development in the intermediate stage can increase carbon intensity through the "scale effect" of expansion, while long-term emission reductions can be achieved based on technological effect caused by the digital finance development in the mature stage.